TECHNIQUES OF DEFEATING STEGANOGRAPHY: A STATE OF ART SURVEY (International Journal of Engineering and Computer Science, 2017)
Steganography is a useful tool that allows covert transmission of information over an overt communications Channel. Combining covert channel exploitation with the encryption methods of substitution ciphers and/or one time pad cryptography, Steganography enables the user to transmit information masked inside of a file in plain view. The hidden data is both difficult to detect and when combined with known encryption algorithms, equally difficult to decipher. This paper discusses the functional areas in the field of Steganography, how Steganography works, what Steganography software is commercially available and what data types are supported, what methods and automated tools are available to aide computer forensic investigators and information security professionals in detecting the use of Steganography , after detection has occurred, can the embedded message be reliably extracted, can the embedded data be separated from the carrier revealing the original file, and finally, propose some methods to defeat the use of Steganography even if it cannot be reliably detected